The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/7900150
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cold Spray Process Inputs to Minimize Porosity and Maximize Hardness of Metal Matrix Composite Coatings on AZ31B Magnesium Alloy

Abstract: In this investigation, the development of an empirical relationship to determine the porosity and microhardness of the coatings through low-pressure cold-sprayed (LPCS) aluminum alloy/alumina metal matrix composite (MMC) deposit. Spray parameters like temperature, standoff distance (SOD), and powder feed rate play an essential part in the determination of the coating effectiveness. In this study, 3 variables, 5 levels of central composite rotatable design (CCD) were used to decrease the total count of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It was found that the addition of Al 2 O 3 solid particles to pure aluminum powder in certain proportions improved the mechanical properties of obtained coatings [15][16][17]. Thus, in [18] it was determined that with the addition of Al 2 O 3 particles, the bond strength of the coating with the magnesium substrate increased.…”
Section: Introductionmentioning
confidence: 97%
“…It was found that the addition of Al 2 O 3 solid particles to pure aluminum powder in certain proportions improved the mechanical properties of obtained coatings [15][16][17]. Thus, in [18] it was determined that with the addition of Al 2 O 3 particles, the bond strength of the coating with the magnesium substrate increased.…”
Section: Introductionmentioning
confidence: 97%
“…These products are the first of their kind, developed in a variety of forms using natural fibers. Krishnudu et al [23] examined the optimization of the reinforcement ratios, and the optimum values of reinforcement are recommended in order to increase the mechanical characteristics [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be concluded that the results of single-factor experiments obtained in the study of multi-factor systems are often of little use for practical application. For the investigation of multi-factor systems, it is most appropriate to use statistical methods of experiment design, which make it possible to obtain models of multi-factor processes with a minimum number of runs [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%